Divine callings: religious sensemaking in the organizational founding process - Scheitle, Christopher P. (Journal of management, spirituality & religion, 2016)
Organizational scholars have not considered the potential power of religion as a sensemaking tool. Religion scholars have wondered whether religious sensemaking is simply a post hoc justification for behavior, or whether it can shape future actions. In this article, we present mixed methods research that gets at the intersection of these issues. In interviews with founders of religious nonprofit organizations, we find that many frame their founding experiences in religious terms, such as believing that God gave them the idea for their organization or attributing certain founding events to divine intervention. We then examine data from a survey of young religious nonprofits and find that reports of personal religious experiences are more common among primary founders compared to other leaders. We also find that those founders reporting certain religious experiences work more hours in the organization, suggesting that sensemaking strategies could have consequences for individuals' behavior.